Globally suitable areas for Lycorma delicatula based on an optimized Maxent model - Zhengxue Zhao; Lin Yang; Xiangsheng Chen (Ecology and Evolution, 2024)
Abstract Lycorma delicatula, a globally invasive pest, has caused considerable economic losses in many countries. Determining the potential distribution range of L. delicatula is crucial for its effective management and control; however, our understanding of this species remains limited. In this study, Maxent model with occurrence records and environmental variables were fit first and then optimized by selecting the best combination of feature classes and regularization multipliers using the lowest score of corrected Akaike information criterion. Subsequently, we predicted global suitable areas for L. delicatula both currently and in the future (2041–2060, 2061–2080, and 2081–2100). The results indicated that the mean temperature of the driest quarter is the most important environmental variable limiting L. delicatula distribution. Currently, the suitable areas are concentrated in East Asia (mainly in China, South Korea, and Japan), central and eastern United States, and southern Europe. Compared with current environmental conditions, in all future climate scenarios, the number of suitable areas for L. delicatula increased. In addition, we revealed that suitable areas are likely to expand northward in the future. Our study results suggest that policymakers and governments should prioritize the development of pest management measures in suitable areas for L. delicatula, especially in high suitable areas, to control this invasive pest and minimize global economic losses.